Cormac McCarthy and the Genre Turn in Contemporary Literary Fiction - James Dorson (European Journal of American Studies)
The wholesale embrace of genre fiction by contemporary literary writers is currently reorganizing the literary field. This essay looks at the role that genre has played in Cormac McCarthy’s fiction since his turn to the Western with Blood Meridian (1985). It assesses his genre fiction vis-à-vis Mark McGurl’s influential study of the importance of creative writing programs for postwar US fiction in The Program Era (2009). In contrast to the modernist aesthetic institutionalized in program era fiction, I argue that the recent genre turn significantly changes the relationship of literary fiction to reality as well as to institutions. I suggest that the turn to genre should be considered the formal response to a crisis in reality, triggered by twenty-first-century reconceptualizations of the world and our place in it, which requires new ways of representing reality. By reading McCarthy’s The Road (2006) alongside Colson Whitehead’s Zone One (2011), I argue that the genre turn in contemporary literary fiction also marks a turn toward institutions, one that both rejects the anti-institutionality of the program era and a return to the modern disciplinary institution in favor of rethinking a value basis for future institutions.